2015
DOI: 10.4070/kcj.2015.45.1.81
|View full text |Cite
|
Sign up to set email alerts
|

Case of Recurrent Ventricular Fibrillations with Osborn Wave Developed during Therapeutic Hypothermia

Abstract: Therapeutic hypothermia (TH) has been used to protect neurological functions in cardiac arrest patient. Although Osborn wave is not pathognomonic of hypothermia, it is a well-known electrocardiogram finding of hypothermic patients. The cellular and ionic mechanisms of the Osborn wave have been suggested, and its relationship to tachyarrhythmias, such as ventricular tachycardia and ventricular fibrillation, is being explored. This case highlights the arrhythmogenic potential of Osborn wave and individual differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 19 publications
0
10
0
1
Order By: Relevance
“…However, there is no clear understanding of the clinical significance of J waves present during accidental hypothermia or TH. Previous reports have demonstrated discrepant data with either no increase in arrhythmogenicity or a higher incidence of ventricular arrhythmias in patients who develop J waves during accidental hypothermia or TH . A recent study examining hypothermia in canine coronary perfused wedge preparations demonstrated increased J‐wave amplitudes when cooling the specimens to 32–34°C .…”
Section: Introductionmentioning
confidence: 95%
“…However, there is no clear understanding of the clinical significance of J waves present during accidental hypothermia or TH. Previous reports have demonstrated discrepant data with either no increase in arrhythmogenicity or a higher incidence of ventricular arrhythmias in patients who develop J waves during accidental hypothermia or TH . A recent study examining hypothermia in canine coronary perfused wedge preparations demonstrated increased J‐wave amplitudes when cooling the specimens to 32–34°C .…”
Section: Introductionmentioning
confidence: 95%
“…This case highlights the arrhythmogenic potential of Osborn waves. [ 7 ] The association of Osborn wave with myocardial ischemia in our patient which was not evident from the ECG but was revealed by highly raised CK-MB levels. Our patient developed sudden cardiac arrest most probably due to ventricular fibrillation which was not documented.…”
mentioning
confidence: 73%
“…While some studies and case reports [5,10,11] found an association of arrhythmia and presence of OW, other studies [7,27,34,35] found no association and considered the presence of OW of limited value as a predictor of malignant ventricular arrhythmias.…”
Section: Osborn Waves and Arrhythmogenecitymentioning
confidence: 98%
“…arrest patients have suggested a possible relation between OW and an increased risk of ventricular arrhythmia [11], while a smaller observational study has failed to confirm this association [12].…”
Section: Accepted Manuscript Introductionmentioning
confidence: 99%